Guest editorial: Special cluster on reconfigurable and multifunctional electromagnetic surfaces for emerging wireless systems - Soh, P. J.; Phan, D. T.; Luo, Q.; Matos, S.; Clemente, A.; Di Renzo, M. (IEEE Antennas and Wireless Propagation Letters, 2025)
The rapid evolution of wireless systems calls for renewals and advancements in technologies for reconfiguring electromagnetic (EM) surfaces, arrays, and (quasi-)periodic apertures to operate in increasingly complex wireless environments. Radically new technologies are foreseen to be needed in the next-generation wireless systems with advanced functionalities in applications, such as communication, sensing, localization, and imaging [1], [2], [3], [4]. Advanced multifunctional EM surfaces/apertures include features, such as anomalous transmission and/or reflection, multiband, multibeam, spatio-temporal features, that potentially result in information EM and analog computing [5], [6], [7], [8], [9]. The need for reconfiguration technologies and multifunctionality in these surfaces necessitates the establishment of new concepts, models, and methodologies in their design, optimization, fabrication, and evaluation. Besides that, new tuning technologies, advanced fabrication techniques, intelligent design/optimization algorithms, and measurement techniques are introduced [10], [11], [12]. These new findings result in advanced multifunctional EM surfaces/apertures with excellent performance, which are capable of profoundly transforming transceiver architectures and significantly improving the quality of current and future wireless systems.